Aspek-aspek Kuantitatif yang Mempengaruhi Kebijakan Pinjaman Daerah (Studi Kasus Kabupaten/Kota di Propinsi Jawa Timur) - Mulyono, Imam (TEMA, 2007)
This paper analyzes the impact of GDP per-capita, populasi, economic growth, PAD, DAU, capital expenditure, and surplus/deficit non financial faktor on muÂ¬nicipal debt behavior. With this aim, we have obtained stratified random sample of 21 cities during a third year period. These data have been used to configure a micro panel to obtain accurate estimates and control for problem such as unÂ¬observed heterogeneity. The main conclusion obtained from this process is that all independ varible are the variable s that best explain the indebtedness of this type of entities Keyword: GDP, economic growth, indebtedness